Flows and Counterflows of Buddhism ‘South of the West’: Australia, New Zealand and Hawai‘i - Halafoff, Anna (Journal of global buddhism, 2022)
Introduction to the JGB Special Focus section, "Flows and Counterflows of Buddhism ‘South of the West’: Australia, New Zealand, and Hawaiʻi." In this special issue, we endeavour to explore horizontal flows and counter flows of Buddhism on ‘paths less travelled’ across the Pacific sea of islands, and ‘South of the West’ (Gibson 1992) rather than the usual ‘from Asia to Europe and the Americas’ story. As such, this special issue fits within the more recent scholarship on the globalisation of Buddhism that seeks to point to a more complex picture of historical and contemporary flows of Buddhist ideas, practices, objects and peoples across the globe.